Source of quartz cement in tight gas sandstone: Evidence from the Upper Triassic Xujiahe Formation in the western Sichuan Basin, SW China - Yu, Yu; Lin, L.; Li, Zhen; Chen, H. (ELSEVIER, 2022)
Quartz cement is a significant authigenic mineral in the tight gas sandstones of the Upper Triassic Xujiahe Formation, fourth member (Xu4 sandstones) in the western Sichuan Basin. Here we report mineralogical, petrological and geochemical data from the Xu4 sandstones to constrain the silica sources of their quartz cements. The quartz cements mainly occur as quartz grain overgrowths and pore-filling quartz cement, with major associated authigenic minerals including calcite, dolomite, illite, kaolinite, and chlorite. The homogenization temperatures of quartz cement fluid inclusions range from 49.2 °C to 143.4 °C and show a multistage continuous precipitation process. Raman spectrometry results show the presence of methane (CH4) and CO2 in quartz cement fluid inclusions. The dissolution of feldspar, the illitization of kaolinite and smectite, as well as the pressure dissolution of quartz grains provided silica sources for quartz cement. The dissolution of feldspar by organic acid (carboxylic acid) is the main silica source for quartz cement in the 80–120 °C interval; the illitization of smectite and kaolinite have different initial temperatures, and both consume potassium. The pressure dissolution of quartz grains results in stylolite formation. The low-temperature quartz cement (<70 °C) is mainly derived from the dissolution of feldspar by meteoric water. At the Late Triassic/Jurassic transition, the uplift of the western basin led to leaching by meteoric water in the upper part of the Xu4 sandstone, forming a weakly acidic fluid with a low K+/H+ ratio and giving this type of sandstone low potassium and sodium concentrations.